Fluorocarbon free and biobased oil and water barrier materials comprising polyelectrolyte complexes

JP2025028272AActive Publication Date: 2025-02-28ORGANOCLICK AB
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024221558
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-10-31
Filing Date
2024-12-18
Publication Date
2025-02-28
Estimated Expiration
2040-10-20

Smart Images

  • Figure 2025028272000001
    Figure 2025028272000001
  • Figure 2025028272000002
    Figure 2025028272000002
  • Figure 2025028272000003
    Figure 2025028272000003
Patent Text Reader

Abstract

To provide compositions of hydrophilic biomaterials that can form several layers on fiber-based materials so that the layers can act synergistically to improve both oil and water barrier capacity of the material with its applied layers.SOLUTION: There is provided an aqueous polyelectrolyte (PEC) composition for application to a fiber-based material for the use of obtaining a barrier coating resistant to oil and water, wherein the composition comprises: (a) from 0.1 to 20% (w / w) of carboxymethyl cellulose (CMC) and from 0.1 to 20% of cationic starch (CS); (b) from 1 to 20% (w / w) of a plasticizer; and (c) from 1 to 15% (w / w) of a pH adjusting agent selected from an acid, a buffering system and a base, and the composition has charge ratio that is equal to or less than 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to compositions comprising anionic and cationic biopolymer polyelectrolytes complexes (PECs) capable of forming a barrier on textile-based materials. [Background technology]

[0002] For example, to increase the oil and water resistance (to form an oil and water barrier) on fibrous materials, such as paper for packaging, it is common to coat them with another polymeric material. Currently, polymers made from fossil materials, such as polyethylene, are used exclusively. In some cases, aluminum foil is combined with plastics to obtain a stronger barrier. Fluorocarbons are also very efficient chemicals for making oil and water repellent fibrous materials, but more and more fluorinated compounds are being banned worldwide due to their toxicity and bioaccumulation. Currently, the packaging / paper industry in particular is looking for new sustainable solutions to form oil and water barriers that meet the criteria of being non-toxic, bio-based, and biodegradable.

[0003] As the attention and demand for bio-based materials increases, so does the interest in finding alternatives to fossil barriers. In the food industry, there is a particular focus on reusability of packaging materials, so finding bio-based alternatives to traditional barriers is particularly important. Furthermore, in the packaging industry, compostability is a key issue for disposable products, so there is a demand for biodegradable barriers.

[0004] PECs are association complexes formed by oppositely charged particles, e.g., polymer-polymer, polymer-drug, and polymer-drug-polymer. These complexes are formed by electrostatic interactions between oppositely charged particles, thus avoiding the use of chemical crosslinkers. Based on their origin, polyelectrolytes are classified into natural, synthetic, and chemically modified biopolymers.

[0005] WO 2015 / 119891 describes a method for forming a rough coating, for example to reduce the adhesive drag of a coated article. The coating comprises a polyelectrolyte complex of one or more cationic polyelectrolytes and one or more anionic polyelectrolytes. However, the coating described in this document is not considered a barrier against oil and water.

[0006] Schnell, C. et al. “Films from xylan / chitosan complexes: preparation and characterization” Cellulose, 2017, vol. 24, 4393~4403 Page, et al., discloses a barrier formed of a cationic polyelectrolyte complex containing xylan and chitosan. The disclosed barrier exhibits barrier properties against water vapor and oxygen. However, it would be advantageous to provide a barrier composition that also exhibits barrier properties against lipid-based compounds such as oils.

[0007] No. 8,747,955 discloses a method for producing food packaging with lipid barrier properties by coatings containing polyelectrolyte complexes consisting of anionic and cationic polymers, such as synthetic polyacrylates and polyacids. However, it would be advantageous to find suitable biologically derived materials capable of forming similarly useful barrier coatings from polyelectrolyte compositions.

[0008] WO 2018 / 038671 discloses compositions of polyelectrolyte complexes consisting of oppositely charged biobased polymers, which are useful as binders in fibre-based materials, textiles, woven or non-woven materials, providing improved strength to the materials.

[0009] Chi, K & Catchmark, M, "Improved eco-friendly barrier materials based on crystalline nanocellulose / chitosan / carboxymethyl cellulose polyelectrolyte complexes," Food Hydrocolloids, 2018, vol. 80, pp. 195-205, discloses a fiber-based material with a single-layer barrier coating against oil and water. The barrier is formed from a composition of polyelectrolyte complexes formed from cationic and anionic biopolymers.

[0010] It would be desirable to further develop PEC compositions derived from charged biopolymers to obtain compositions that can be used to obtain controlled barriers from biodegradable fiber materials against both lipids, grease, or oils and water-based materials, particularly but not exclusively for the purpose of protecting food. It is clear to those skilled in the art from common knowledge that water- and oil-repellent barrier materials are also useful for dirt repellency in appropriate situations. Furthermore, it is understood that these types of barrier materials provide an increased oxygen barrier.

[0011] For many reasons, it is desirable to use starch, and in particular cationic starch, to create a sustainable and highly efficient barrier against oil and water. The invention presented below relies on the general insight that polyelectrolyte complexes (PECs) provide synergistic effects from cationic and anionic polymers in a variety of situations. Summary of the Invention

[0012] It is a general object of the present invention to use hydrophilic biomaterials to form barrier structures useful for both oil-based and water or water-based products.

[0013] One of the objectives of the present invention is to provide a hydrophilic biomaterial composition that can be formed into several layers on a fiber-based material, where the layers can act synergistically to improve the barrier properties of the material against oil and water.

[0014] A particular object of the present invention is to provide a fiber-based material having an oil and water barrier based on a composition of biodegradable polyelectrolyte complexes of cationic and anionic biopolymers that contains only ingredients and additives that are generally approved for use in contact with food.

[0015] It is also an object of the present invention to obtain an oil and water barrier that has controlled adhesion of the applied barrier and therefore high resistance to degradation or dissolution of the barrier, while still having controlled heat sealability.

[0016] In one general first aspect, the invention relates to a textile material with an oil and water barrier coating, the material being provided with a barrier from at least two layers formed from at least one composition comprising a polyelectrolyte complex (PEC) of a cationic biopolymer and an anionic biopolymer. The presence of the two layers is synergistic, providing improved resistance to both oil and water compared to the same material with a single layer of the at least one composition. Preferably, each of the two layers provides a lower add-on (g / m2) when applied to the textile material from the at least one composition than the add-on when a single layer of the at least one composition is applied. 2 (in units).

[0017] By improvement in this embodiment is meant that for the material, increased resistance to oil and water is noticeable and can be observed in standard tests such as the KIT test according to T 999pm-96 for oil and the COBB method according to ISO 536:191(E) for water.

[0018] Fiber-based materials, as used herein, include cellulose-based materials, such as those found in various types of paper, paperboard, corrugated board, wrapping paper, other specialty papers, containers, molded pulp or other applications, cardboard, fabrics, and woven and nonwoven materials. The nonwoven materials may generally include synthetic or biofibers, such as fibers, polymeric fibers, and mixtures thereof, including, but not limited to, airlaid nonwovens, drylaid nonwovens, spunbond nonwovens, spunlace nonwovens, wetlace nonwovens, meltblown nonwovens, and wetlaid nonwovens.

[0019] In the context of the present invention, oil or grease barrier refers to the repellency or antiwicking properties of a material against oil, grease, fat, or other oleophilic agents or organic solvents, such as those commonly used by the KIT test. Many such tests are well known to those skilled in the art, for example in applied paper technology, a non-limiting example being TAPPI T559 for grease resistance.

[0020] In one embodiment of the invention, the PEC of at least one composition comprises a cationic biopolymer selected from cationic starch (CS) and / or chitosan, and an anionic biopolymer selected from at least one of alkaline lignin, lignosulfonic acid, or polysaccharides, in particular sodium carboxymethylcellulose (CMC), alginic acid, pectin, carrageenan, gum arabic, hemicellulose, xanthan gum, and nanocrystalline cellulose (NCC), where alginic acid and lignosulfonic acid are preferably present as sodium salts.

[0021] In one embodiment of the present invention, the material includes a barrier comprising two layers formed from two compositions including a polyelectrolyte complex (PEC) of CS and CMC, the two compositions may include 0.1-20% (w / w) CMC and 0.1-20% CS, and preferably 0.5-10% (w / w) CMC and 0.5-20% CS.

[0022] In one embodiment of the present invention, at least one composition of the multi-layer barrier has a designated pH value and includes a pH adjusting agent consisting of an acid, a buffer system, and a base. According to this embodiment, the acid is one or more of an organic acid and an inorganic acid. The organic acid is selected from one or more of acetic acid, acetylsalicylic acid, adipic acid, ascorbic acid, aspartic acid, benzenesulfonic acid, camphorsulfonic acid, citric acid, dihydroxyfumaric acid, ethanesulfonic acid (esylic acid), formic acid, glycolic acid, glutamic acid, glyoxylic acid, hydrochloric acid, lactic acid, malic acid, malonic acid, maleic acid, mandelic acid, mesylic acid, oxalic acid, para-toluenesulfonic acid, pentanoic acid, phthalic acid, propionic acid, pyruvic acid, salicylic acid, sulfuric acid, tartaric acid, triflic acid, any amino acid, levulinic acid, and succinic acid. The inorganic acid is, for example, any of the hydrogen halides: hydrochloric acid (HCl), hydrobromic acid (HBr), hydroiodic acid (HI), or halogen oxoacids: hypochlorous acid, chloric acid, perchloric acid, periodic acid, and the corresponding compounds for bromine and iodine, or any of the sulfuric acid (H2SO4), sulfamic acid, fluorosulfuric acid, nitric acid (HNO3), phosphoric acid (H3PO4), fluoroantimonic acid, fluoroboric acid, hexafluorophosphoric acid, chromic acid (H2CrO4), or boric acid (H3BO3). Preferably, the acid is present in the composition constituting the layer in an amount of 0.01 to 30% (w / w), preferably the acid is selected from citric acid, lactic acid, oxalic acid, and tartaric acid, more preferably the acid is 5 to 15% (w / w) of citric acid and / or lactic acid. The acid preferably provides a pH of 2-4.

[0023] The pH adjuster in said aspect of the invention may be a buffer system, such that at least one composition comprises 0.01-30% (w / w) of an acid-base pair, preferably a corresponding acid-base pair that allows a pH between 2 and 9, more preferably 1-15% (w / w) of said acid-base pair. In one embodiment, the composition comprises 1-10% (w / w) of citric acid and 1-10% (w / w) of tribasic citric acid, preferably in equal amounts.

[0024] The pH adjuster in this aspect of the invention may alternatively be a base, said base being sodium bicarbonate (NaHCO 3 ) is preferred, and it is preferable to give a pH value of 8 to 9.

[0025] In one embodiment of the invention, the two compositions contain PECs having the same CS-CMC relative amounts, ie, CS and CMC are present in the same percentages (by weight) within the two compositions.

[0026] In one embodiment of the invention, at least one of the compositions of the multi-layer barrier comprises a plasticizer, preferably said plasticizer is a polyol type plasticizer, more preferably said plasticizer is glycerol and / or sorbitol present in an amount of 1-20% (w / w).

[0027] In one embodiment of the invention, at least one of the compositions of the multi-layer barrier comprises additives selected from ammonium zirconium carbonate; preservatives; defoamers; foaming agents; wetting agents; coalescent agents; catalysts; surfactants; emulsifiers; crosslinking agents; wet strength additives such as epichlorohydrin; rheology modifiers; fillers; non-ionic polymers; dyes and pigments.

[0028] In one embodiment of the invention, the material has a barrier of at least two applied layers with a KIT value of 5 or more as measured according to T 999 pm-96 and a COBB60 value of 50 or less as measured according to ISO 536:191(E).

[0029] In one aspect of the invention, the material has a barrier in which the first layer is made of a composition having a first pH value and the second layer is made of a composition having a second pH value, preferably the second layer is made of a composition having a lower pH value than the composition forming the first layer. In one embodiment, the composition for the first layer comprises a buffer system as outlined above, and the composition for the second layer comprises an acid as outlined above. In yet another particular embodiment, the first layer is formed of a composition comprising 5-20% (w / w) CS, 1-5% (w / w) CMC, and a buffer system having a pH value of 3-6, the buffer system comprising an acid-base pair selected from citric acid and the corresponding carboxylates of citric acid, and lactic acid and the corresponding carboxylates of lactic acid, and the second layer is formed of a composition comprising 5-20% (w / w) CS, 1-5% (w / w) CMC, and an acid selected from citric acid and lactic acid, and having a pH value of 2-3. The first and second layers are formed, for example, from two compositions having the same CS-CMC relative amounts (weight / weight). In one example of this embodiment, the composition forming the first layer contains 5-15% (weight / weight) of citric acid and tribasic citric acid, and the composition forming the second layer contains 5-15% (weight / weight) of citric acid. In this embodiment, it is preferred that the first layer is an inner layer in the barrier, and the second layer is an outer layer in the barrier.

[0030] In one embodiment of the invention, the PEC of at least one composition has a charge ratio of less than or equal to 1. Charge ratio refers to the overall charge of the PEC formed from the cationic and anionic biopolymers and is further defined in the Exemplification section herein.

[0031] In another embodiment of the present invention, the charge ratio of the PEC in at least one composition is about 1 or greater than 1. One skilled in the art can select the relationship of the cationic biopolymer and the ionic biopolymer to obtain a net charge of the PEC close to neutral or anionic charge. For example, the concentration of the anionic biopolymer CMC can be increased relative to the cationic biopolymer, for example CS. It is also contemplated that different brands of cationic biopolymers with different charge densities can be selected to control the charge ratio of the resulting PECs. The following detailed description and examples of the present invention provide further guidance to one skilled in the art to control the charge density of the PEC composition of the present invention.

[0032] In one embodiment of the invention, the material has a barrier comprising at least one layer of at least one composition comprising a polyelectrolytes complex (PEC) of a cationic biopolymer and an anionic biopolymer, and at least one layer comprising an amino-functional siloxane or a layer comprising a hydrophobic agent such as a wax. A suitable composition for forming a layer comprising an amino-functional siloxane is an emulsion composition disclosed in WO 2018 / 048342 (incorporated herein by reference), to which conventional layer-forming additives can be optionally added. A suitable acidic emulsion composition for a layer comprising a hydrophobic material can be found in WO 2018 / 038670 (incorporated herein by reference), comprising an amino-functional siloxane, a hydrolyzable alkylsilane and water. Such compositions include PECs with cationic and anionic biopolymers having a charge ratio of 1 or less, and one or more fatty compounds selected from oils, waxes, and other lipids or hydrophobic agents. In one embodiment of this aspect, the material includes a barrier having two layers as outlined anywhere above, and an additional layer comprising an amino-functional siloxane as described herein, or a layer comprising a hydrophobic agent.

[0033] According to yet another aspect, the present invention relates to an aqueous polyelectrolyte (PEC) composition for application to textile materials for use in obtaining an oil- and water-resistant barrier coating, said composition comprising: (a) 0.1-20% (w / w) CMC and 0.1-20% CS, preferably 0.5-10% (w / w) CMC and 0.5-20% CS, providing PECs with a charge ratio of 1 or less; (b) 1-20% (w / w) plasticizer, preferably sorbitol; and (c) 1-15% (w / w) pH adjuster selected from acids, buffer systems, and bases.

[0034] In one embodiment, the composition comprises 5-20% (w / w) CS, 1-5% (w / w) CMC, and 1-15% (w / w) of a buffer system consisting of an acid-base pair, preferably the corresponding acid-base pair is from an organic acid, more preferably the buffer system is selected from citric acid / corresponding carboxylate of citric acid and lactic acid / corresponding carboxylate of lactic acid. Preferably, the pH of the composition is 3-6. Also preferably, the composition comprises equal amounts (w / w) of citric acid and tribasic citric acid.

[0035] In yet another embodiment, the composition comprises 5-20% (w / w) CS, 1-5% (w / w) CMC, and an organic or inorganic acid that provides a pH of the composition of 1-3, preferably the acid is present in an amount of 0.01-30% (w / w), more preferably the acid is selected from citric acid, lactic acid, oxalic acid and tartaric acid, more preferably the acid is 5-15% (w / w) citric acid and / or lactic acid.

[0036] In yet another embodiment, the composition comprises 5-20% (w / w) CS, 1-5% (w / w) CMC, and a base to bring the pH of the composition to 8-9, preferably the base is sodium bicarbonate (NaHCO 3 ).

[0037] The compositions exemplified above may further include additives selected from ammonium zirconium carbonate; preservatives; defoamers; foaming agents; wetting agents; coalescent agents; catalysts; surfactants; emulsifiers; crosslinking agents; rheology modifiers; fillers; non-ionic polymers; dyes and pigments.

[0038] Yet another aspect of the invention relates to a kit having at least two compositions comprising: (a) 0.1-20% (w / w) CMC and 0.1-20% CS, preferably 0.5-10% (w / w) CMC and 5-20% CS, providing PECs with a charge ratio of 1 or less, (b) 1-20% (w / w) plasticizer, preferably sorbitol, and (c) 1-15% (w / w) pH adjuster selected from an acid, a buffer system, and a base. The kit is useful for forming a barrier on a textile material and for obtaining an oil and water resistant barrier coating, and comprises a first compartment comprising a first composition having a buffer system, and a second compartment comprising a second composition having a lower pH than the first composition and comprising an acid. The first composition comprises 5-20% (w / w) CS, 1-5% (w / w) CMC, and a buffer system consisting of 1-15% (w / w) acid-base pair, preferably the corresponding acid-base pair is from an organic acid, more preferably the buffer system is selected from citric acid / corresponding carboxylate of citric acid and lactic acid / corresponding carboxylate of lactic acid, even more preferably the composition comprises equal amounts (w / w) of citric acid and tribasic citric acid and has a pH of 3-6. The second composition comprises 5-20% (w / w) CS, 1-5% (w / w) CMC and an organic or inorganic acid that brings the pH of the composition to 1-3, preferably the acid is present in an amount of 0.01-30% (w / w), preferably the acid is selected from citric acid, lactic acid, oxalic acid and tartaric acid, more preferably the acid is 5-15% (w / w) citric acid and / or lactic acid.

[0039] The kit with at least two compositions according to the present invention is usually assembled to produce the material of the present invention with improved barrier, to keep the compositions separate during transportation and storage, and to support easy industrial application of the compositions.To this end, the compositions are stored separately in separate compartments of the kit, which may be conventional or suitable separate containers available to those skilled in the art.The kit may also include a user's manual to support the application and manufacturing methods as outlined in the following part of the specification.

[0040] In yet another aspect, the present invention relates to a method of making a material according to any of the aspects or embodiments disclosed above, comprising the steps of applying a first layer to the material with a composition comprising a polyelectrolyte complex (PEC) of a cationic biopolymer and an anionic biopolymer, optionally drying the material at a temperature between 15 and 90° C. until essentially dry, followed by applying a second composition or applying a second layer over the first layer, again using the same composition; and, optionally ly) curing the material. In one embodiment, the curing is carried out at a temperature between 20°C and 200°C, more preferably between 50°C and 200°C, and most preferably between 90°C and 180°C.

[0041] The method is carried out by applying the first and second compositions by at least one of the following process techniques: spraying, roll coating; foulard coating; dip coating; screen coating; padding, impregnation, or using a size press; direct coating methods such as knife coating, blade coating, wire wound bar coating, round bar coating, and crushed foam coating; indirect coating methods such as mayer rod coating, direct roll coating, kiss coating, gravure coating, and reverse roll coating; preferably, the application is by roll coating or foulard coating.

[0042] In one embodiment of the invention, when the method is performed, the second composition applied is the same as the first composition.

[0043] In another embodiment of the present invention, the first composition has a different pH value than the second composition. Preferably, the pH of the first composition is higher than that of the second composition. Also preferably, the first composition comprises a buffer system consisting of 5-20% (w / w) CS, 1-5% (w / w) CMC, and 1-15% (w / w) of an acid-base pair, preferably the corresponding acid-base pair is from an organic acid, more preferably, the buffer system is selected from citric acid / corresponding carboxylate of citric acid and lactic acid / corresponding carboxylate of lactic acid, and even more preferably, the composition comprises equal amounts (w / w) of citric acid and tribasic citric acid and has a pH of 3-6. Also preferably, said second composition comprises 5-20% (w / w) CS, 1-5% (w / w) CMC and an organic or inorganic acid that brings the pH of the composition to 1-3, preferably said acid being present in an amount of 0.01-30% (w / w), preferably said acid being selected from citric acid, lactic acid, oxalic acid and tartaric acid, more preferably said acid being 5-15% (w / w) citric acid and / or lactic acid. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0044] Methods, Equipment, Chemicals and Formulations

[0045] Test equipment: pH was measured using a VWR pHenomenal pH1000H with a Hamilton Polilyte Lab Temp BNC electrode (calibrated with pH 4, 7 and 10 buffer solutions). · Particle charge was measured using a Mutek PCD 02 device. Mixing of the preparations and pulp suspensions was performed using an IKA overhead mixer (either a Eurostar digital IKA-Werke or an IKA RW28 basic) with a propeller stirrer. Homogenization of the preparation was performed using an IKA T25 digital Ultra-Turrax. The materials were applied using a bench coater with an iron rod (referred to as "coater") or a Wichelhaus WI-MU 505 A horizontal padder (referred to as "padder"). Weight measurements were performed using an XT 220A Precica Swissmade balance.

[0046] method: [Method 1] Solid content (SC) 5 g of powder or 10 g of preparation was placed in an aluminum cup and placed in an oven at 105° C. overnight. The solid content was calculated using equation (4).

number

[0047] [Method 2] Charge density and charge ratio The charge density was measured using a Mutek PCD 02 device. The charge (symbol: q, unit: meqv) was calculated using equation (1).

number

number

number

[0048] [Method 3] Preparation of the preparation Cationic starch was dissolved in water at 60-70°C in a homogenizer in the presence of biocide or used as pre-cooked starch concentrate. CMC was added to the dissolved cationic starch and dissolved in a homogenizer. When additives were used, they were added and mixed in the final step.

[0049] [Method 4] Applying to paper using a roll The composition was applied manually to sheets of material using a cylindrical iron rod, and the treated paper was dried in an oven at 150°C for 2-3 minutes.

[0050] [Method 5] KIT Exam / T 599 pm-96 The grease resistance test of paper and paperboard was measured according to T 559 pm-96, with a ranking from 1 (poor barrier) to 12 (best possible barrier).

[0051] [Method 6] COBB method / ISO 536:191(E) Water absorption for 60 seconds or 1800 seconds (COBB 60 or COBB 1800 ) is ISO 536:191(E).

[0052] [Method 7] Impregnating paper using a padder The formulation was poured between the rolls of the padder at a pressure of 0.1 MPa and a speed of 11.6 rpm. The treated paper was dried in an oven at 150°C for 2-3 minutes.

[0053] [Method 8] Spray test Determination of the resistance of fabrics to surface wetting (spray test): European Standard EN 24 920 (ISO 4920:1981). Principle: A specified amount of water is sprayed onto a textile specimen mounted on a ring. The specimen is placed at a 45° angle to the nozzle. The centre of a standardised nozzle is placed at a defined distance from the centre of the specimen. A defined amount of water is poured into a reservoir placed above and in communication with the nozzle. The spray rating is determined visually or photographically. A graded spray rating of ISO 1 to 5 corresponds to 50 to 100% of the specimen resisting wetting.

[0054] Chemicals, materials and compositions: The chemicals used in the experiments are listed in Tables 1 and 2. [Table 1] [Table 2]

[0055] The papers and boards used in the experiments are listed in Tables 3 and 4. [Table 3] [Table 4]

[0056] The compositions used in the experiments are listed in Table 5. The weight percentage of biopolymer in the compositions in Table 5 is calculated taking into account the respective solid content in Table 1. In Table 5, whenever CS and CMC are used alone as references, the formulation is based on 10-15 wt.% biopolymer dissolved in tap water with a small amount of biocide. [Table 5]

[0057] [Example of the present invention] Example 1. Comparative test of barrier performance of biopolymer alone compared to PEC To determine whether cationic starch and carboxymethyl cellulose each provide barrier performance and how this compares to their combination in a PEC, the following test was performed: Type 2 paper was coated according to method 4. Two layers were applied and the results are shown in Table 6. [Table 6]

[0058] Example 2. The importance of the number of layers Type 2 paper with 1 ply and high add-on, or 12.5 g / m2 or 1 Composition 8 was coated according to method 4 in 2 layers with 4.2 g / m2. See Table 7. [Table 7]

[0059] This result highlights not only that performance is load dependent, but that adding two layers of sufficient load is highly advantageous for achieving high grease resistance as indicated by the KIT number compared to a single layer.

[0060] Example 3. Application of PEC Compositions of Various Charges Since the PEC can have a variety of charges, it was decided to evaluate what effect different charges have on grease resistance. See Table 8. Type 2 paper was applied with two layers of each composition according to Method 4. The KIT values ​​were then recorded using Method 5. [Table 8]

[0061] Example 4. Combination of Different PEC Composition Layers Some compositions containing cationic starch give a sticky / tacky surface to the target material, which may or may not be desired. This example shows how different compositions can be selected for the first and second layers to reduce the stickiness and improve the KIT and / or COBB values. Application method 4 was applied to type 2 paper. The results are seen in Table 9. A more hydrophobic commercial binder called OC-Biobinder 5401 was selected to combine with composition 1 of the present invention. [Table 9]

[0062] It is concluded that the order of application affects the tackiness / stickiness, COBB and KIT values ​​of the processed material. The order of application can be selected depending on the desired material properties.

[0063] Example 5. Effect of adding plasticizer on KIT and COBB values Carbohydrate-based polymers are known to be structurally rigid and therefore the hand and appearance of the treated material is expected to be rigid as well. To improve the folding properties of the treated material, reduce stiffness, reduce paper wrinkles after drying, and increase the softness of the barrier coating, a common bio-based plasticizer was used and its amount was optimized. See Table 10. Type 2 paper was coated by method 4 with the composition specified in Table 10. [Table 10]

[0064] In addition to its softening effect on the barrier coating, an amount of sorbitol was found to favorably affect the KIT and COBB values ​​of the treated material.

[0065] Example 6. Effect of Different pH on Barrier Properties Tests were conducted to see if pH adjusters (acid and base) could be used as additives to control adhesion while maintaining KIT barrier properties. Grade 2 paper was coated with two layers by method 4, as shown in Table 11. See Table 11. [Table 11]

[0066] It can be seen that papers treated with formulations adjusted to a lower pH compared to the original composition are much less sticky than compositions adjusted to a higher pH compared to the original composition, which is an important feature in some cases, such as in heat sealing processes.

[0067] Another observation made upon addition of citric acid monohydrate to composition 6 was that the PEC composition was much more dilutable in the sense that it did not form a large precipitate when water was added to the formulation.

[0068] Example 7. Plasticized and pH adjusted compositions on various cellulosic materials In further examples, the combination of plasticizers and pH adjusting additives was investigated. Compositions 12 and 13 were evaluated on type 2 paper, molded pulp paper, and type 1 and 2 paperboard. All materials were coated with two layers of each composition by method 4. [Table 12]

[0069] The combination of the PEC with the plasticizer and pH adjusting additives gave very encouraging results in terms of both COBB and KIT values, thus providing a good water and grease barrier on the coated material. It was also clear that application of composition 12 produced a good grease barrier, while composition 13 produced a good water barrier, and most importantly, the coatings did not appear to interfere with each other and worked synergistically.

[0070] Example 8. Combination of PEC and non-PEC coatings on various materials To further expand the application of the present invention, textile materials were coated. A white polyester fabric with a basis weight of 150 g / m2 was coated with each of PEC compositions 1 and 2 by method 4, and then further coated with commercial hydrofobizing products OC-aquasil Tex 310 or OC-aquasil Tex 303 by method 7. The results are shown in Table 13. [Table 13]

[0071] It can be concluded that the present invention is capable of forming a good barrier against water and grease even on textile products which have a much lower density than, for example, paper. [Note] The present invention has the following aspects: <1> ~ <38> Also included. <1> 1. A fiber-based material having an oil and water barrier coating, the barrier comprising at least two layers formed from at least one composition comprising a polyelectrolyte complex (PEC) of a cationic biopolymer and an anionic biopolymer, and a pH adjusting agent comprising a buffer system, the fiber-based material comprising an oil and water barrier coating, The fiber-based material, wherein the two layers provide improved resistance to both oil and water compared to the same material provided with a single layer of the at least one composition. <2> The cationic biopolymer is selected from cationic starch (CS) and chitosan, and the anionic biopolymer is selected from at least one of alkaline lignin, lignosulfonic acid, or polysaccharides, in particular sodium carboxymethylcellulose (CMC), alginic acid, pectin, carrageenan, gum arabic, hemicellulose, and nanocrystalline cellulose (NCC), where alginic acid and lignosulfonic acid are preferably present as sodium salts; <1> The material described in. <3> The two layers are formed of two compositions including a polymer electrolyte composite (PEC) of CS and CMC; <2> The material described in. <4> The two compositions contain 0.1-20% (w / w) CMC and 0.1-20% CS, preferably 0.5-10% (w / w) CMC and 0.5-20% CS; <3> The material described in. <5> At least one of the compositions includes a pH adjuster selected from an acid and a base; <1> ~ <4> 2. The material according to claim 1 , <6> the acid is one or more organic or inorganic acids and is present in the layer-forming composition in an amount of 0.01-30% (w / w), preferably the acid is selected from citric acid, lactic acid, oxalic acid and tartaric acid, more preferably the acid is 5-15% (w / w) of citric acid and / or lactic acid, <5> The material described in. <7> the buffer system provides the composition with 0.01-30% (w / w) of an acid-base pair, preferably a corresponding acid-base pair that tolerates a pH of 2-9; <5> The material described in. <8> The composition comprises 1-10% (w / w) citric acid and 1-10% (w / w) tribasic citric acid, preferably in equal amounts; <7> The material described in. <9> The base is sodium bicarbonate (NaHCO3 ), <5> The material described in. <10> The two compositions contain PECs having the same relative amounts of CS-CMC; <3> ~ <9> 2. The material according to claim 1 , <11> At least one of the compositions forming the layers comprises a plasticizer, preferably said plasticizer is a polyol type plasticizer, more preferably said plasticizer is sorbitol present in an amount of 1-20% (w / w); <1> ~ <10> 2. The material according to claim 1 , <12> at least one layer-forming composition comprises additives selected from ammonium zirconium carbonate; preservatives; defoamers; foaming agents; wetting agents; coalescent agents; catalysts; surfactants; emulsifiers; crosslinking agents; rheology modifiers; fillers; non-ionic polymers; dyes and pigments; <1> ~ <11> 2. The material according to claim 1 , <13> the barrier has a KIT value of 5 or greater, as measured in accordance with T 999 pm-96, and a COBB60 value of 50 or less, as measured in accordance with ISO 536:191(E); <1> ~ <12> 2. The material according to claim 1 , <14> a first layer is formed from a composition having a first pH value and a second layer is formed from a composition having a second pH value, preferably the second layer being formed from a composition having a lower pH value than the composition providing the first layer; <1> ~ <13> 2. The material according to claim 1 , <15> The composition for the first layer is <7> or <8> and the composition for the second layer comprises a buffer system according to <6> The acid according to <14> The material described in. <16> A first layer is formed from a composition having a pH value of 3 to 6, comprising 5 to 20% (wt / wt) CS, 1 to 5% (wt / wt) CMC, and a buffer system comprising an acid-base pair selected from citric acid and a carboxylate of citric acid, lactic acid and the corresponding carboxylate of lactic acid; and a second layer is formed from a composition having a pH value of 1 to 3, comprising 5 to 20% (wt / wt) CS, 1 to 5% (wt / wt) CMC, and an acid selected from citric acid and lactic acid. <15> The material described in. <17> The first and second layers are formed from two compositions having the same relative amounts (wt / wt) of CS-CMC; <14> ~ <16> 2. The material according to claim 1 , <18> The composition forming the first layer contains 5 to 15% (weight / weight) of citric acid and tribasic citric acid, and the composition forming the second layer contains 5 to 15% (weight / weight) of citric acid; <16> or <17> The material described in. <19> the first layer being an inner layer of the barrier and the second layer being an outer layer of the barrier; <14> ~ <18> 2. The material according to claim 1 , <20> The charge ratio of the PEC is 1 or less. <1> ~ <19> 2. The material according to claim 1 , <21> having a barrier comprising at least one layer comprising an amino-functional siloxane or a layer comprising a hydrophobic agent such as a wax or oil; <1> ~ <20> 2. The material according to claim 1 , <22> <14> ~ <21> and <21> The additional layer according to claim 1, <21> The material described in. <23> (a) 0.1-20% (w / w) CMC and 0.1-20% CS, preferably 0.5-10% (w / w) CMC and 10-20% CS, providing PECs with a charge ratio of 1 or less; (b) 1 to 20% (w / w) of a plasticizer, preferably sorbitol, and (c) an aqueous polymer electrolyte complex (PEC) composition for application to a textile material for use in obtaining an oil- and water-resistant barrier coating, comprising 1-15% (w / w) of a pH adjuster selected from an acid, a buffer system, and a base. <24> a buffer system consisting of 5-20% (w / w) CS, 1-5% (w / w) CMC, and 1-15% (w / w) of an acid-base pair, preferably the corresponding acid-base pair is derived from an organic acid, more preferably the buffer system is selected from citric acid and the corresponding carboxylate of citric acid, and lactic acid and the corresponding carboxylate of lactic acid; <23> The composition described in <25> Contains equal amounts (wt / wt) of citric acid and tribasic citric acid, <24> The composition described in <26> pH value is 3-6; <24> or <25> The composition described in <27> 5-20% (w / w) CS, 1-5% (w / w) CMC, and an organic or inorganic acid that brings the pH of the composition to 1-3, preferably said acid being present in an amount of 0.01-30% (w / w), preferably said acid being selected from citric acid, lactic acid, oxalic acid and tartaric acid, more preferably said acid being 5-15% (w / w) citric acid and / or lactic acid. <23> The composition described in <28> The composition comprises 5-20% (w / w) CS, 1-5% (w / w) CMC, and a base that adjusts the pH of the composition to 8-9, preferably sodium bicarbonate (NaHCO 3 ), <23> The composition described in <29> ammonium zirconium carbonate; preservatives; defoamers; foaming agents; wetting agents; coalescent agents; catalysts; surfactants; emulsifiers; crosslinking agents; rheology modifiers; fillers; non-ionic polymers; dyes and pigments, <23> ~ <28> 13. The composition according to any one of claims 1 to 12. <30> For use in obtaining oil- and water-resistant barrier coatings, for application to textile materials, <23> A kit comprising at least two compositions according to the present invention, The kit comprises a first compartment having a first composition having a buffer system, and a second compartment having a second composition comprising an acid having a lower pH than the first composition. <31> The first composition <24> ~ <26> 2. The composition according to claim 1 , wherein the second composition is <27> The composition according to claim 1, <30> The kit according to claim 1, <32> applying a first layer to the material with a first composition comprising a polyelectrolyte complex (PEC) of a cationic biopolymer and an anionic biopolymer; Optionally drying the material at a temperature between 15 and 90°C; applying a second layer over the first layer using a second composition; and hardening the material at a temperature between 15 and 90°C; Including, <1> ~ <22> 2. A method for producing the material described in any one of claims 1 to 11. <33> The curing is carried out at 20°C to 200°C, more preferably 90°C to 200°C, and most preferably 90°C to 180°C. <32> The method described above. <34> applying said first and second compositions by at least one of the group consisting of: spraying, roll coating; foulard coating; dip coating; screen coating; padding, impregnation, size pressing; direct coating methods such as knife coating, blade coating, wire wound bar coating, round bar coating, and crushed foam coating; indirect coating methods such as mayer rod coating, direct roll coating, kiss coating, gravure coating, and reverse roll coating; preferably, said application is by roll coating or foulard coating. <32> or <33> The method described above. <35> the second composition is the same as the first composition; <32> ~ <34> 2. The method according to claim 1 , <36> the first composition has a different pH value than the second composition; <32> ~ <34> 2. The method according to claim 1 , <37> the first composition has a higher pH value than the second composition; <36> The method described above. <38> The first composition <24> ~ <26> 2. The composition according to claim 1 , wherein the second composition is <27> The composition according to claim 1, <37> The method described above.

Claims

1. (a) 0.1-20% (w / w) carboxymethylcellulose (CMC) and 0.1-20% cationic starch (CS) to provide a polyelectrolyte complex (PEC) with a charge ratio of 1 or less; (b) 1-20% (w / w) of a plasticizer; and (c) an aqueous polyelectrolyte complex composition for application to a textile material for use in obtaining an oil- and water-resistant barrier coating, comprising 1-15% (w / w) of a pH adjuster selected from an acid, a buffer system, and a base.

2. 2. The composition of claim 1, comprising 0.5-10% (w / w) CMC and 10-20% (w / w) CS.

3. The composition of claim 1 , wherein the plasticizer is sorbitol.

4. 2. The composition of claim 1, comprising a buffer system consisting of 5-20% (w / w) CS, 1-5% (w / w) CMC, and 1-15% (w / w) of an acid-base pair.

5. The composition of claim 4, wherein the acid-base pair is a corresponding acid-base pair derived from an organic acid.

6. 5. The composition of claim 4, wherein the buffer system is selected from citric acid and the corresponding carboxylate of citric acid, and lactic acid and the corresponding carboxylate of lactic acid.

7. 5. The composition of claim 4 comprising equal amounts (w / w) of citric acid and tribasic citric acid.

8. The composition according to claim 4, having a pH value of from 3 to 6.

9. 10. The composition of claim 1 comprising 5-20% (w / w) CS, 1-5% (w / w) CMC, and an organic or inorganic acid to provide a pH of the composition of 1-3.

10. The composition of claim 9, wherein the acid is selected from citric acid, lactic acid, oxalic acid and tartaric acid.

11. The composition according to claim 9, wherein the acid is 5-15% (w / w) citric acid and / or lactic acid.

12. 10. The composition of claim 1 comprising 5-20% (w / w) CS, 1-5% (w / w) CMC, and a base to provide a pH of the composition of 8-9.

13. The base is sodium bicarbonate (NaHCO 3 13. The composition of claim 12, wherein

14. 10. The composition of claim 1, further comprising additives selected from at least one of the following: ammonium zirconium carbonate; preservatives; defoamers; foaming agents; wetting agents; coalescent agents; catalysts; surfactants; emulsifiers; crosslinking agents; rheology modifiers; fillers; non-ionic polymers; dyes and pigments.

Citation Information

Patent Citations

  • JP1982501634A

  • Method of surface treatment for imparting hydrophilicity to aluminum material

    JP1994264001A

  • Processing agent for textile product

    JP2000239970A

  • Additive for paper manufacturing use, and method for producing paper

    JP2005068587A

  • Papermaking method and paper

    JP2007277795A